Influence of Dairy co-operatives in Rural Development in India: a case study of Banas Dairy, Banaskantha district, Gujarat. - CHAUDHARI, NEETI; MINAMPATI, DR. VENKAT RAM REDDY (The journal of contemporary issues in business and government, 2021)
We have traversed a path few have dared to. We are continuing on a path still fewer have the courage tofollow. We must pursue a path that even fewer can dream to pursue. Yet we must, because we hold in trustthe aims and aspirations of millions of our countrymen. I am confident – as I know you are – that with thenation’s dairy farmers by our side we cannot fail! Let us therefore resolve that however fulfilling our firsttwenty five years have been, in the next twenty five years we will transform the lives of millions more,opening for them the door to an India that is the land of our dreams. Dr. Verghese Kurien Co-operative is a form of community organization where all the members work together in order to fulfill their common needs. All the members of this organization are obliged to maintain their democratic, participatory and transparent decision making procedure because it is jointly owned, and commonly operated on the value of self-help, mutual help and self- responsibility (National Cooperative Federation Nepal, 2010). The members ofacooperative have a common goal in order to meet their economic, social and cultural needs under the control of joint approach by its own members so that their members are directly responsible for benefiting themselves and ultimately to the society at large. While pricing the milk and milk products co-operatives play an important role. A cooperative is an enterprise owned by and operated for the benefit of those members and users. The dairy co-operatives operated by the farmers often use a complete milk distribution system from the point of procurement to the consumers where it is marketed. Also make a bargaining capacity for the price with the traders. It represents in that level of decision where different rules and regulations are formed. Cooperative also can make the decision to change the marketing system of the product and the nature of product from one to another in order to maintain highest return to the members and users Now-a-days, Indian dairy industry has to face the global dairy markets. At this point of changing times,Gujarat State is undergoing considerable modernization with latest technology. It will be right to study and analyze the performance of the district co-operative milk unions of Gujarat and its socio economic impact on rural people's livelihood. The present study will focus on performance of co-operative dairy industry of Gujarat State which are engaged in processing and selling of milk and milk products as well as performing the social and welfare programs in the communities they own. For this study, we choose to pick a leading co-operative dairy unit(Banas Dairy) performanceis analyzing co-operative growth and the way the rural community benefited out of it.